A randomized placebo-controlled trial of delayed-release dimethyl fumarate in patients with relapsing-remitting multiple sclerosis from East Asia and other countries - Saida, Takahiko; Yamamura, Takashi; Kondo, Takayuki; Yun, Jang; Yang, Minhua; Li, Jie; Mahadavan, Lalitha; Zhu, Bing; Sheikh, Sarah I (BMC neurology, 2019)
BACKGROUND: Delayed-release dimethyl fumarate (DMF) has demonstrated efficacy and a favorable benefit-risk profile in phase 2 and 3 studies that enrolled predominantly white patients with relapsing-remitting multiple sclerosis (RRMS). In this study (APEX, Part I), we evaluated the efficacy/safety outcomes of DMF in a predominantly East Asian population of patients with RRMS. METHODS: In this 24-week, randomized, double-blind, placebo-controlled phase 3 study, 225 patients, 142 of which were East Asian (63.4%), were enrolled: Japan (n = 114), South Korea (n = 20), Taiwan (n = 8), the Czech Republic (n = 42), and Poland (n = 40). Key exclusion criteria included diagnosis of neuromyelitis optica spectrum disorder. Stratified by country, patients were randomized 1:1 to receive DMF 240 mg twice daily or placebo. Clinical assessments, including neurological examination and EDSS scoring, were conducted at baseline and at weeks 12 and 24. RESULTS: A total of 213 patients (95.1%) completed the study. From weeks 12 - 24, the total number of new gadolinium-enhancing (Gd+) lesions was reduced by 84% (p < 0.0001) in DMF compared with placebo. For the secondary endpoint, from baseline to week 24, the total number of new Gd+ lesions was reduced by 75% and the mean number of new/newly enlarging T2 hyperintense lesions was reduced by 63% (both p < 0.0001). Flushing and flushing-related symptoms, and gastrointestinal events were adverse events related to DMF treatment. Efficacy and safety results in the Japanese subgroup and the East Asian subgroup (which included patients from Japan, Taiwan, and South Korea) were consistent with the overall study population. CONCLUSION: The strong efficacy and favorable benefit-risk profile of DMF extends to Japanese, and more broadly, East Asian patients with RRMS. TRIAL REGISTRATION: This trial is registered on ClinicalTrials.gov (identifier: NCT01838668 ), April 20, 2013 (retrospectively registered). The registration can be found at the following URL: https://clinicaltrials.gov/ct2/show/NCT01838668.
Keywords: Randomized clinical trial; gadolinium; Humans; Asia, Eastern; lidé středního věku; Delayed-Action Preparations; Dimethyl Fumarate; Delayed-release dimethyl fumarate; Dálný východ; dimethyl fumarát; Double-Blind Method; Gadolinium; Female; Polsko; dospělí; výsledek terapie; dvojitá slepá metoda; lidé; Poland; Japan; imunosupresiva; Adult; Immunosuppressive Agents; Multiple sclerosis; Multiple Sclerosis, Relapsing-Remitting; ženské pohlaví; relabující-remitující roztroušená skleróza; East Asia; Male; Middle Aged; Magnetic resonance imaging; Treatment Outcome; Czech Republic; léky s prodlouženým účinkem; Česká republika; mužské pohlaví